Successful resection of a neuroendocrine tumor in the gallbladder: a case report - Hideo Tomihara; Kazuhiko Hashimoto; Tomoko Wakasa; Hajime Ishikawa; Tomoyuki Tsujimoto; Atsushi Gakuhara; Shuichi Fukuda; Katsuya Ohta; Kotaro Kitani; Jin-ichi Hida; Yoshio Ohta; Masao Yukawa (Surgical Case Reports)
Abstract Background Gallbladder neuroendocrine tumors (GB-NETs) are extremely rare, representing only 0.5% of all NETs because no neuroectodermal cells are present in the gallbladder. In 2019, the World Health Organization updated the classification of NETs based on their molecular differences. The mutation status of DAXX and ATRX has been added to the criteria for well-differentiated NETs. Case presentation A 50-year-old man presented to our hospital for further examination of a gallbladder polyp. He had no right quadrant pain, fever, jaundice, weight loss, or carcinoid syndrome-related symptoms. The patient hoped to avoid cholecystectomy. During the 3-year observation period, the polyp gradually increased in size from 8.3 to 9.9 mm. He decided to undergo surgery, and whole cholecystectomy was successfully performed. Immunohistochemical staining revealed positivity for chromogranin A, synaptophysin, and CD56. The Ki-67 index was < 3%. Taken together, these results led to a diagnosis of a grade 1 GB-NET. We also performed immunohistochemical staining of DAXX and ATRX, which revealed that DAXX protein expression was negative. The patient’s postoperative course was uneventful, and he developed no recurrence for 8 years after surgery. Conclusion We experienced a very rare case of GB-NET. Obtaining a correct preoperative diagnosis is quite difficult at the first evaluation. A GB-NET should be considered as a differential diagnosis of gallbladder tumors.